2005
DOI: 10.1111/j.1365-3032.2005.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to environmental stress in altitudinal populations of two Drosophila species

Abstract: Opposite clinal variation for desiccation and starvation tolerance are observed in four altitudinal populations (219-2202 m), each of two sympatric and cold adapted species: Drosophila takahashii and Drosophila nepalensis from northern India. The high-altitude populations are more tolerant to desiccation than those from lower altitudes, whereas the reverse trend occurs for starvation tolerance. The magnitude of tolerances are significantly high in D. nepalensis, which is better adapted to cold conditions. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…This is true of D. melanogaster from the east coast of Australia, where in several populations in response to summer acclimation temperatures, individuals showed greater desiccation resistance than flies exposed to constant or winter temperatures (Hoffmann et al, 2005b). Similar declines in desiccation resistance with increasing treatment temperature have also been found for D. takahashii and D. nepalensis (Parkash et al, 2005). Here, we found that when exposed to 29°C, either as adults or as pupae, adult G. pallidipes had significantly reduced rates of water loss compared to flies held at 21°C or 25°C (and similar to results described in Terblanche et al, in press).…”
Section: Discussionmentioning
confidence: 50%
“…This is true of D. melanogaster from the east coast of Australia, where in several populations in response to summer acclimation temperatures, individuals showed greater desiccation resistance than flies exposed to constant or winter temperatures (Hoffmann et al, 2005b). Similar declines in desiccation resistance with increasing treatment temperature have also been found for D. takahashii and D. nepalensis (Parkash et al, 2005). Here, we found that when exposed to 29°C, either as adults or as pupae, adult G. pallidipes had significantly reduced rates of water loss compared to flies held at 21°C or 25°C (and similar to results described in Terblanche et al, in press).…”
Section: Discussionmentioning
confidence: 50%
“…Thus, the findings recorded for D. ananassae provide evidence that the quality and quantity of nutrients consumed by organisms have strong impact on stress resistance. Studies on resistance to different kinds of stress in different species of Drosophila occurring in India have also been reported by Parkash and coworkers (Parkash and Shamina 1994;Parkash and Munjal 1999;Parkash et al 2005;. The desiccation tolerance and starvation resistance exhibit opposite latitudinal clines and significant differentiation among Indian geographical populations of D. kikkawai.…”
Section: Ecological Adaptationsmentioning
confidence: 86%
“…Observed variations in the investigated physiological traits show regular clines along latitude as well as altitude. The occurrence of latitudinal clines for various traits (morphological, cytological and ecophysiological) on different continents is often considered to be adaptive evolutionary responses to climatic conditions of the origin of populations (Dobzhansky 1948; Stalker and Carson 1948; Mettler et al 1977; Prevosti et al 1985; Watada 1986; Parkash and Munjal 1999; Parkash et al 2005). However, climatic conditions are complex and it can be difficult to identify environmental selective factors.…”
Section: Discussionmentioning
confidence: 99%